Potential Strategies for Kidney Regeneration With Stem Cells: An Overview - Tsuji, Kenji; Kitamura, Shinji; Wada, Jun (Frontiers in Cell and Developmental Biology, 2022)
Kidney diseases are a of major health problem worldwide. Despite advances in drug therapies, they are only capable of slowing the progression of kidney diseases. Accordingly, potential kidney regeneration strategies with stem cells have begun to be explored. There are two different directions for regenerative strategies, de novo whole kidney fabrication with stem cells, and stem cell therapy. De novo whole kidney strategies include: (i) decellularized scaffold technology, (ii) 3D bioprinting based on engineering technology, (iii) kidney organoid fabrication, (iv) blastocyst complementation with chimeric technology, and (v) the organogenic niche method. Meanwhile, stem cell therapy strategies include (i) injection of stem cells, including mesenchymal stem cells, nephron progenitor cells, adult kidney stem cells and multi-lineage differentiating stress enduring cells, and (ii) injection of protective factors secreted from these stem cells, including growth factors, chemokines, and extracellular vesicles containing microRNAs, mRNAs and proteins. Over the past few decades, there have been remarkable step-by-step developments in these strategies. Here, we review the current advances in the potential strategies for kidney regeneration using stem cells, along with their challenges for possible clinical use in the future.